Pemanfaatan AI (Artificial Intelligence) Untuk Meningkatkan Kinerja Kelurahan Sukasari - Tri Santoso; Sulistianto SW; Syahriani; Ardian Dwi Praba (CV. Multi Kreasi Media, 2024)
AI (Artificial Intelligence) is a field of computer science that focuses on creating solutions to cognitive cases or those related to human intelligence. Among the many AI technologies that are currently viral is ChatGPT. Utilizing AI technology can make daily work easier and also help Sukasari district staff or employees who have difficulty responding to questions asked by residents quickly, precisely and accurately. The methods used in implementing this activity are starting from planning activities, providing materials and activity modules, implementing training and direct practice and evaluation. The aim of this activity is to provide participants with skills in creating and using chatGPT-based chatbox applications properly. It is hoped that the results of this activity will increase their skills in using applications with AI technology, especially chatbox applications based on chatGPT.